Artificial Intelligence Emergence in Agriculture - Upadhyaya, Aurobind (Indian Farming, 2019)
Agriculture, one of the prime sector and foundation of economy is under immense pressure. Increasing the total production by 70% in order to meet the world’s demand in the next 30 years is an objective imperiled by reducing resources, climatic changes and other man-made and natural threats. According to UN Food and Agriculture Organization, the population will increase by 2 billion by 2050. However, only 4% additional land will come under cultivation by then.